Nutrient acquisition efficient rootstocks improve zinc nutrition of top-grafted citrus trees on calcareous soil - Xie, Jiawei; Xiong, Huaye; Niu, Runzheng; Wang, Yuheng; Wang, Yuehong; Lali, Mohammad Naeem; Zhao, Jingkun; Shi, Xiaojun; Rennenberg, Heinz (Frontiers in Plant Science, 2025)
IntroductionZinc deficiency is a common issue in top-grafted citrus trees. Citrus scions top-grafted on rootstocks may exhibit zinc deficiency due to reduced mineral absorption and transport. Therefore, selecting the appropriate rootstock is thought to be crucial for Zn nutrition of top-grafted citrus trees.MethodsTo test this assumption, we performed top-grafting of citrus scions using Poncirus trifoliata (L.) Raf. and Citrus junos (Sieb.) Tanaka as rootstocks and analyzed growth, Zn nutrition, and physiological traits of the top-grafted citrus trees.Results and discussionThe results indicated that, compared with the Poncirus trifoliata (L.) Raf. rootstock, the C. junos (Sieb.) Tanaka rootstock significantly increased the Zn level in new leaves, mature leaves, stems, and roots by 81.69%, 66.18%, 97.52%, and 45.94%, respectively, and positively influenced growth, photosynthetic efficiency, and foliar carbon and nitrogen metabolite concentrations in the top-grafted citrus trees. Metabolome analysis of leaves revealed that intermediates of the glyoxylate, dicarboxylate, ascorbate and aldarate metabolic pathways were responsive to different Zn levels. Thus, C. junos (Sieb.) Tanaka rootstock stimulated plant growth, boosted Zn acquisition, and enhanced the physiological performance of top-grafted citrus plants. The mechanisms by which C. junos (Sieb.) Tanaka rootstocks improve the performance of citrus plants require further research.